UTILIZATION OF EPANET IN REDUCING FLOODING ON JALAN GADING KIRANA TIMUR - Mohammad Imamuddin; Tanjung Rahayu; Jihan Melanie Syaputri (International Journal of Civil Engineering and Infrastructure, 2025)
Jalan Gading Kirana Timur, North Jakarta, experienced significant flooding problems due to an inadequate drainage system. This study aims to analyze the performance of the drainage pipeline network using EPANET v.2.0 software and compare the simulation results with manual calculations. Quantitative descriptive methods are used to collect data through literature studies and field surveys. The results of the analysis showed that the flow speed in the pipeline was above the set minimum limit, but the headloss value reached 19.38 m/km, far exceeding the maximum limit of 10 m/km. This indicates that water cannot flow properly to the disposal site, potentially causing inundation and flooding. Manual calculations and EPANET simulations show consistency in total head and headloss, with total heads at junction 2 being 32.07 m. Recommendations for improvements include increasing pipeline capacity to reduce headloss and the use of EPANET as an aid in planning more effective drainage systems. This research is expected to provide input for the community and the government in flood mitigation efforts on Jalan Gading Kirana Timur, North Jakarta.Keywords: flooding, drainage system, EPANET.